English Learning Strategies Employed By The Eleventh Grade Students of SMAN 1 Kediri - Laila, Nur; Arafiq; Elmiana, Dewi Satria; Sujana, I Made (Journal of Authentic Research, 2026)
This study aims to determine the English learning strategies used by eleventh-grade students of SMAN 1 Kediri and the difficulties faced by these students. The population of this study was 132 eleventh-grade students, and the sample consisted of 12 students selected using purposive sampling. According to Oxford (1990), there are six learning strategies classified into two categories, namely direct and indirect strategies. Direct strategies include memory strategies, cognitive strategies, and compensation strategies. Meanwhile, indirect strategies consist of metacognitive strategies, affective strategies, and social strategies. This study was conducted using a sequential mixed-method design, using questionnaires and interviews as data collection techniques. The dominant learning strategies used by students were compensation strategies (mean = 3.75, high category), cognitive strategies (mean = 3.51, high category), and social strategies (mean = 3.41, high category). Ten out of twelve students reported that grammar was the most common difficulty they encountered in learning English, while the other two students stated that pronunciation was the most difficult aspect. These difficulties are attributed to language differences, limited exposure, and a lack of speaking practice.